Diagnosis, evolution and treatment of a patient with pyomyositis - Larissa Figueiredo Vieira; Gustavo Olivieri Barcellos; Christian Tales Elias; Marco Tulio Rodrigues da Cunha; Isabella da Silva Idelfonso; Pedro Augusto Fávaro Amaral (Revista Brasileira de Cirurgia Plástica, 2023)
Pyomyositis is a deep muscle infection of bacterial origin and subacute, which can evolve with multiple intramuscular abscesses. Despite being characterized as an affection of tropical zones, its incidence in temperate zones has been increasing due to immunosuppression factors, such as infection by the human immunodeficiency virus (HIV) and some types of immunosuppressive treatments. Even though it has been known for over a century, it is a rare and potentially serious condition that can lead to septic shock and death. This is a case report of a descriptive nature, which found the relevance of knowledge about this condition for an early diagnosis, enabling positive prognostic repercussions.